Determination of minimum fluidization velocity for gas-solid beds by experimental data and numerical simulations - De Souza Braun, Meire Pereira; Navarro, Helio Aparecido; Palma, Geraldo Luiz [UNESP]; Varoto, Paulo Sergio (ASME International, 2011)
The purpose of this work is to predict the minimum fluidization velocity Umf in a gas-solid fluidized bed. The study was carried out with an experimental apparatus for sand particles with diameters between 310μm and 590μm, and density of 2,590kg/m3. The experimental results were compared with numerical simulations developed in MFIX (Multiphase Flow with Interphase eXchange) open source code [1], for three different sizes of particles: 310mum, 450μm and 590μm. A homogeneous mixture with the three kinds of particles was also studied. The influence of the particle diameter was presented and discussed. The Ergun equation was also used to describe the minimum fluidization velocity. The experimental data presented a good agreement with Ergun equation and numerical simulations. Copyright © 2011 by ASME.
Keywords: Different sizes; Ergun equation; Experimental apparatus; Gas-solid; Gas-solid fluidized bed; Homogeneous mixtures; Minimum fluidization velocity; Multiphase flow with interphase exchanges; Open-source code; Particle diameters; Sand particles; Exhibitions; Fluidized beds; Mechanical engineering; Multiphase flow; Computer simulation